PENGEMBANGAN PERANGKAT PEMBELAJARAN METODE MAIN PERAN BERBASIS BUDAYA LOKAL "SIRONDO-RONDOI" UNTUK ANAK USIA DINI - Siti Maria Ulfah; Asdar Asdar; Nurul Amaliah (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2024)
This research aims to develop an effective and efficient Mandar local culture-based role-playing learning tool to improve early childhood social development in Majene Regency. Children at the age of early childhood education, especially in kindergarten, need to interact with their environment to develop their social skills. Through social interaction, children gain experiences that build their knowledge, as stated by Vigotsky. However, the results of observations at Fathinah Kindergarten show that some children have difficulties in working together and socializing. Therefore, this study uses a role-playing method based on the local Mandar culture, namely sirondo-rondoi, in role-playing activities with children aged 5-6 years. The research methods used include observation, interviews, documentation, and questionnaires. The data collected is analyzed qualitatively and quantitatively using the ADDIE model which will produce a product of a development model that plays a role in introducing. The results show that the use of local culture-based role-playing methods significantly improves children's social development. The learning tools of the local culture-based sociodrama method have met the validity criteria with the achievement of the average children's activeness in the good category so that children's activities during learning activities meet the ideal criteria, which are in the high category.